Pengaruh Religiusitas, Persepsi Resiko, dan Sikap Terhadap Intensi Kepatuhan Wajib Pajak dalam Lapor SPT Pajak Pribadi Melalui E-Filing Tahun 2023 di Provinsi DKI Jakarta - Silaban, Delta S; Febyansyah, Andar (MES Management Journal, 2025)
This research examines the influence of religiosity, risk perception, attitude, and the e- Filing system on tax compliance intention of individual taxpayers in filing Annual Tax Returns in DKI Jakarta Province. The study aims to analyze the relationships between these variables in the context of digital transformation in Indonesian tax administration. The research employs a quantitative approach with Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis technique. Primary data were collected through questionnaires distributed to 155 individual taxpayers in DKI Jakarta. The results show that religiosity and risk perception significantly influence taxpayers' attitudes, and these attitudes directly affect tax compliance intention. However, religiosity and risk perception do not have a direct effect on tax compliance intention. The research also finds that the e- Filing system does not moderate the relationships between religiosity, risk perception, and attitude toward tax compliance intention. These findings indicate that taxpayers' attitudes serve as the primary mediator in determining tax compliance intention. This research provides theoretical contributions to the development of a tax compliance model that integrates personal and technological factors. Practically, the results can serve as input for the Directorate General of Taxes in formulating tax policies that focus on developing positive taxpayer attitudes, strengthening tax education, and improving the e-Filing system to enhance tax compliance in Indonesia.